Handbook of social and emotional learning research and practice - Durlak, Joseph A.; Domitrovich, Celene E.; Weissberg, Roger P.; Gullotta, Thomas P. (New York The Guilford Press, 2015)
"The burgeoning multidisciplinary field of social and emotional learning (SEL) now has a comprehensive and definitive handbook covering all aspects of research, practice, and policy. The prominent editors and contributors describe state-of-the-art intervention and prevention programs designed to build students' skills for managing emotions, showing concern for others, making responsible decisions, and forming positive relationships. Conceptual and scientific underpinnings of SEL are explored and its relationship to children's and adolescents' academic success and mental health examined. Issues in implementing and assessing SEL programs in diverse educational settings are analyzed in depth, including the roles of school-and district-level leadership, teacher training, and school-family partnerships"--Provided by publisher.
"This book explores the educational status of social and emotional learning (SEL) and the ways that educational systems accommodate an SEL perspective. SEL can be conceptualized in at least three different ways: (1) as a human development process and field of study involving the acquisition of skills, knowledge and attitudes; (2) as a set of specific programs; or (3) as a general educational approach, movement or policy. This book is intended for educators, psychologists, and others who work with children and schools. Programs and practices are designed to promote the mental health and academic success of all students by helping them to develop skills needed for managing emotions, showing concern for others, making responsible decisions, and forming positive relationships in and out of school"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Affective education -- United States; Social learning -- United States